2017
DOI: 10.29252/sjnmp.3.2.49
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the correlation between Spiritual Intelligence and communication skillsamong nursing students

Abstract: Background & Aim: The key to playing role in the nursing profession is the proper communication and is, in fact, the basic part of nurses' careers in looking after the patients. Recognizing the factors related to communication skills of nursing students, including spiritual intelligence, can be used to increase the quality of care. The purpose of this study was to investigate the correlation between spiritual intelligence and communication skills of nursing students in Kurdistan University of Medical Sciences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The findings of this study showed a statistically significant and positive correlation between nurses’ communication competence and spiritual intelligence. In line with the present findings, some scholars [ 34 – 36 ] confirm the positive and significant relationship between communication skills and spiritual intelligence. On the other hand, George [ 39 ] considers the effectiveness of interpersonal communication as one of the main features of spiritual intelligence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study showed a statistically significant and positive correlation between nurses’ communication competence and spiritual intelligence. In line with the present findings, some scholars [ 34 – 36 ] confirm the positive and significant relationship between communication skills and spiritual intelligence. On the other hand, George [ 39 ] considers the effectiveness of interpersonal communication as one of the main features of spiritual intelligence.…”
Section: Discussionsupporting
confidence: 92%
“…Using their spiritual intelligence, nurses can solve problems, give meaning to their work and activities, become aware of the meaning of their performance, and find out their more valid actions [ 28 ]. The effect of spiritual intelligence on the self-efficacy of nurses [ 29 33 ] and their competence acquisition in this field [ 34 – 36 ] is a topic that has been mentioned in previous studies. This intelligence, due to the use of the internal resources of the individual to increase the capacity of attention, tolerance, and adaptability, can help to develop the understanding of nurses in the field of personal and work communication and to improve the level of their competence and relational self-efficacy [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sabzianpour and Sunaryo also showed a positive and signi cant relationship between spiritual intelligence and quality of nursing care, Caring Behavior (23,34). In a study, Salawati Ghasemi demonstrated a signi cant relationship between spiritual intelligence and communication skills of nurses (22). In their study, Salmani, Arsang-Jang and Haryono found a positive and signi cant relationship between spiritual intelligence and nurses' support for patients and also between spiritual intelligence, ethical decision making of nurses and nurses' organisational commitment.…”
Section: Discussionmentioning
confidence: 93%
“…Review of the literature showed that not only it is considered in individual areas but also it is regarded in organizational areas. Also, it seems that increasing number of research in the eld of spirituality may be due to its tangible signi cant effect on improving individual and organizational performance (14,21,22).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that previous studies conducted on SI and ethical reasoning and care behavior of nurses have not yet been able to reveal the various dimensions of the issue. Also, it seems that a growing number of studies conducted on spirituality and ethics may be attributed to their tangible significant impacts on increasing both individual performance and organizational performance ( 21 , 22 ). In addition, the correlation between the study variables using Structural equation modeling (SEM) can be one of the strengths of this study.…”
Section: Introductionmentioning
confidence: 99%